Translation Techniques Found in Sign Boards in Tourist Areas in Bali - Tengku Amin Diwan Waruwu; I Gusti Ayu Agung Dian Susanthi; Rahmat Gaho (Austronesian: Journal of Language Science & Literature, 2025)
In international tourism hubs such as Bali, bilingual or multilingual sign boards help ensure that foreign tourists can understand public information, navigate spaces safely, and engage meaningfully with their environments. This research investigates the translation techniques used, and the types of equivalence applied in translating Sign Board in tourist areas in Bali. The research employs qualitative descriptive method. A total of 45 sign boards were analyzed in this study. The results show that in using LT, translators tend to retain the structure and lexical meaning of the source language directly into the target language. The dominance of the LT indicates that the translated texts are common public signs that are informative, concise, direct, and do not require denotative creativity. The language used on signboards typically consists of instructions, prohibitions, or directions, making semantic precision more important than stylistic considerations. In addition, some other data employ the CT technique, especially in longer texts, warnings, or messages that require greater clarity within the cultural context of the target audience. The WFW technique appears only in very simple terms, whereas FT is used for texts that require more flexible meaning adaptation. Then, DE is the most dominant technique, accounting for approximately 75.5% of the total data. The dominance of DE indicates that the translator prioritizes naturalness, readability, and the effectiveness of the message for English readers. Conversely, FE is used in more technical contexts or when the source language structure can be preserved without affecting the meaning.